2018
DOI: 10.1038/s41598-018-19419-6
|View full text |Cite
|
Sign up to set email alerts
|

An optimised protocol for platelet-rich plasma preparation to improve its angiogenic and regenerative properties

Abstract: Although platelet-rich plasma (PRP) is used as a source of growth factors in regenerative medicine, its effectiveness remains controversial, partially due to the absence of PRP preparation protocols based on the regenerative role of platelets. Here, we aimed to optimise the protocol by analysing PRP angiogenic and regenerative properties. Three optimising strategies were evaluated: dilution, 4 °C pre-incubation, and plasma cryoprecipitate supplementation. Following coagulation, PRP releasates (PRPr) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 44 publications
3
99
0
5
Order By: Relevance
“…However, as compared with nondiabetic controls, angiogenic activities of platelets remain unaltered in T2D patients (Miao, Zhang, Huang, & Li, 2016). Some authors have also found that PRP from diabetic patients releases more VEGF and increases proliferation and migration of endothelial cells at larger extent, compared with PRP from healthy donors (Etulain et al, 2018; Karina et al, 2019). Notably, solid evidence supports the use of autologous PRP for the treatment of diabetic foot ulcers (Hirase, Ruff, Surani, & Ratnani, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, as compared with nondiabetic controls, angiogenic activities of platelets remain unaltered in T2D patients (Miao, Zhang, Huang, & Li, 2016). Some authors have also found that PRP from diabetic patients releases more VEGF and increases proliferation and migration of endothelial cells at larger extent, compared with PRP from healthy donors (Etulain et al, 2018; Karina et al, 2019). Notably, solid evidence supports the use of autologous PRP for the treatment of diabetic foot ulcers (Hirase, Ruff, Surani, & Ratnani, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the released factors were evaluated for both our composite scaffold and PRP releasate (PRPr) in different cell types (endothelial, mesenchymal stromal cells, macrophages, fibroblasts, and keratinocytes) since all of them have key roles during different stages of wound healing (Gurtner et al, 2008;Eming et al, 2014). There is vast literature suggesting that PRP supports endothelial cell proliferation and induces angiogenesis/vascularization both in vitro and in vivo (Kakudo et al, 2014;Anitua et al, 2015;Notodihardjo et al, 2015;Etulain et al, 2018;Romaldini et al, 2019;Samberg et al, 2019). Our work corroborates those findings, but, importantly, shows that this activity is maintained within a biomaterial scaffold with proven regenerative potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, the temperature, the leukocyte, and the plasma volume might influence therapeutic results have not been well determined. Recent investigation showed that adding saline instead of plasma (which contains anti‐platelet factors) to the platelet pellets could improve the therapeutic effects on would healing and angiogenesis in animal model . In this study, a volume of 10 mL PRP was used simply because we can inject PRP at 20 sites through most of the bladder wall.…”
Section: Discussionmentioning
confidence: 99%